Genetic Characterization of the Exceptionally High Heat Resistance of the Non-toxic Surrogate Clostridium sporogenes PA 3679 - Butler, Robert R.; Schill, Kristin M.; Wang, Yun; Pombert, Jean-François (Frontiers in Microbiology, 2017)
Clostridium sporogenes PA 3679 is a non-toxic endospore former that is widely used as a surrogate for Clostridium botulinum by the food processing industry to validate thermal processing strategies. PA 3679 produces spores of exceptionally high heat resistance without botulinum neurotoxins, permitting the use of PA 3679 in inoculated pack studies while ensuring the safety of food processing facilities. To identify genes associated with this heat resistance, the genomes of C. sporogenes PA 3679 isolates were compared to several other C. sporogenes strains. The most significant difference was the acquisition of a second spoVA operon, spoVA2, which is responsible for transport of dipicolinic acid into the spore core during sporulation. Interestingly, spoVA2 was also found in some C. botulinum species which phylogenetically cluster with PA 3679. Most other C. sporogenes strains examined both lack the spoVA2 locus and are phylogenetically distant within the group I Clostridium, adding to the understanding that C. sporogenes are dispersed C. botulinum strains which lack toxin genes. C. sporogenes strains are thus a very eclectic group, and few strains possess the characteristic heat resistance of PA 3679.